2013
DOI: 10.1111/jnc.12360
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone releasing hormone (GHRH) signaling modulates intermittent hypoxia‐induced oxidative stress and cognitive deficits in mouse

Abstract: Intermittent hypoxia (IH) during sleep, such as occurs in obstructive sleep apnea (OSA), leads to degenerative changes in the hippocampus, and is associated with spatial learning deficits in adult mice. In both patients and murine models of OSA, the disease is associated with suppression of growth hormone (GH) secretion, which is actively involved in the growth, development and function of the central nervous system (CNS). Recent work showed that exogenous GH therapy attenuated neurocognitive deficits elicited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…IH is the main feature of OSA (Kohler and Stradling, 2010;Nair et al, 2013;Quintero et al, 2013), leading to injuries to a variety of organs and systems (Gami et al, 2004;Kendzerska et al, 2014;Marin et al, 2012;Nicholl et al, 2012;Peppard et al, 2000;Redline et al, 2010;Sakaguchi et al, 2011;Tan et al, 2014). Accumulating clinical evidences have indicated that OSA is an independent risk factor for loss of kidney function (Ahmed et al, 2011;Chou et al, 2011;Nicholl et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…IH is the main feature of OSA (Kohler and Stradling, 2010;Nair et al, 2013;Quintero et al, 2013), leading to injuries to a variety of organs and systems (Gami et al, 2004;Kendzerska et al, 2014;Marin et al, 2012;Nicholl et al, 2012;Peppard et al, 2000;Redline et al, 2010;Sakaguchi et al, 2011;Tan et al, 2014). Accumulating clinical evidences have indicated that OSA is an independent risk factor for loss of kidney function (Ahmed et al, 2011;Chou et al, 2011;Nicholl et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, how IH impairs kidney remains unclear. IH is believed to induce oxidative stress (Chen et al, 2014;Nair et al, 2013;Quintero et al, 2013) which contributes to renal injury (Zheng et al, 2011). MT has been defined as a potent antioxidant that effectively protects kidney from oxidative damage (Kojima et al, 2009;Shimazu et al, 2013;Sun et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although continuous hypoxia promotes the increased expression and activity of both molecules (71), acute IH upregulates HIF-1␣ and downregulates HIF-2␣ protein via calpains (125). Furthermore, contrary to sustained hypoxia, long-term IH during sleep has been reported to induce early activation of HIF-1␣ in the brain that is then followed by reductions in HIF-1␣ expression or its target genes over time (41,99,122). If we consider that HIF-2␣ regulates the transcription of several antioxidant enzymes including SOD-2 (169), the downregulation of HIF-2␣ in the context of acute IH may also contribute to increases in ROS via insufficient transcription of antioxidative enzymes.…”
Section: Maladaptation To Ih: Pathological Effectsmentioning
confidence: 99%